2006
DOI: 10.1074/jbc.m513730200
|View full text |Cite
|
Sign up to set email alerts
|

Mutations Affecting β-Tubulin Folding and Degradation

Abstract: Revertants of a colcemid-resistant Chinese hamster ovary cell line with an altered (D45Y) ␤-tubulin have allowed the identification of four cis-acting mutations (L187R, Y398C, a 12-amino acid in-frame deletion, and a C-terminal truncation) that act by destabilizing the mutant tubulin and preventing it from incorporating into microtubules. These unstable ␤-tubulins fail to form heterodimers and are predominantly found in association with the chaperonin CCT, suggesting that they cannot undergo productive folding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 38 publications
2
18
0
Order By: Relevance
“…That phenomenon is not unique, as it has been already reported for other antimicrotubule agents by Schimming et al (1999). We hypothesise that cells with alkylated b-tubulin might be eliminated quickly in vivo via phagocytosis and/or ubiquitin proteasome degradation pathways, as described previously (Krysko et al, 2006;Liu et al, 2006;Wang et al, 2006). Likewise, the tumoricidal concentration of ICEU necessary to kill cells should be higher as compared to in vitro when one considers the interrelated influence of physiological parameters such as perfusion, necrosis, cell density and interstitial pressure that may affect the diffusion of the drug into the tumoral tissues and the neoplastic cells.…”
Section: Discussionmentioning
confidence: 70%
“…That phenomenon is not unique, as it has been already reported for other antimicrotubule agents by Schimming et al (1999). We hypothesise that cells with alkylated b-tubulin might be eliminated quickly in vivo via phagocytosis and/or ubiquitin proteasome degradation pathways, as described previously (Krysko et al, 2006;Liu et al, 2006;Wang et al, 2006). Likewise, the tumoricidal concentration of ICEU necessary to kill cells should be higher as compared to in vitro when one considers the interrelated influence of physiological parameters such as perfusion, necrosis, cell density and interstitial pressure that may affect the diffusion of the drug into the tumoral tissues and the neoplastic cells.…”
Section: Discussionmentioning
confidence: 70%
“…It has recently been shown that beta-tubulin with a p.L187R mu11tation, fails to form heterodimers, and consequently does not incorporate into MTs. This was shown to be a consequence of an impaired interaction with cofactors involved in the tubulin folding pathway [Wang et al, 2006]. The same molecular impairment may underlie the pathology of the individual with the I188L mutation.…”
Section: Discussionmentioning
confidence: 97%
“…Note that the relevance of this mechanism for regulated mRNA stability under steady-state conditions and for specifying cellular tubulin content is still unclear. Indeed, extensive studies of selected variants of CHO cells with acquired resistance to taxol have provided examples of cell lines in which the taxol/colchicine-responsive autoregulatory mechanism does not compensate for alterations in tubulin heterodimer content and/or partitioning (Boggs and Cabral, 1987;Barlow et al, 2002;Wang et al, 2006). Moreover, it has also been shown that increased transcription is the major mechanism behind increased tubulin heterodimer content during pressure-induced hypertrophy of cardiac cells, and changes in mRNA stability could not be detected (Narishige et al, 1999).…”
Section: Role Of Unassembled and Free Tubulin Concentrations In Autormentioning
confidence: 99%
“…However, detailed analyses of cell lines with acquired resistance to the microtubule-stabilizing drug taxol have shown that substantial changes in tubulin heterodimer content, monomer-polymer partitioning, or both may occur without compensatory changes in tubulin synthesis (Boggs and Cabral, 1987;Barlow et al, 2002). Thus, the significance of autoregulation of tubulin mRNA stability for the normal regulation of tubulin heterodimer content and partitioning is still unclear, and it has been proposed that autoregulation is not activated by small changes in polymerization (Wang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%